High temperature phase equilibria in the Fe-Co-Cu-Si system pertinent to slag cleaning - Banda, Wezi (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2006.